Neural crest cells: Evolution, embryonic bases and craniofacial development. Systematic literature review - Moreno-Gómez, Freddy A.; Pachajoa, Harry (Revista Estomatología, 2015)
The neural crest cells are a population of embryonic stem cells that differentiate from the neuro-ectoderm and whose appearance constitutes an evolutionary innovation allowed vertebrates develop different morpho-functional structures to adapt from asuspensivorous eating style to a predatory style, much more efficient. This systematic literature review describes the essential role of neural crest cells in the evolutionary and embryonic development of the craniofacial structures of the vertebrates.For this purpose we searched PubMed through the Medical Subject Headings (MeSh) “neural crest” combined with the terms “neurulation, evolution, embryonic and fetal development, craniofacial development” through the Boolean connectors“AND” y “+”. Key words: Neurulation, neutral plata, neural crest cells, embryonic and fetal development, craniofacial development.